High-Mobility Group Box 1 Contributes to Cerebral Cortex Injury in a Neonatal Hypoxic-Ischemic Rat Model by Regulating the Phenotypic Polarization of Microglia - Sun, Yanyan; Hei, Mingyan; Fang, Zhihui; Tang, Zhen; Wang, Bo; Hu, Na (Frontiers in Cellular Neuroscience, 2019)
Neonatal hypoxic-ischemic (HI) encephalopathy is a severe disease for which there is currently no curative treatment. Recent evidence suggests that high-mobility group box 1 (HMGB1) protein can promote neuroinflammation after stroke in adult rodents, but its role in perinatal hypoxic-ischemic brain damage (HIBD) remains largely uninvestigated. In the present work, the potential role of HMGB1 in the pathogenesis of HIBD was explored. A HIBD model was established in postpartum day 7 rat pups. HMGB1 expression, the cellular distribution of HMGB1, and microglial activation were all evaluated. Glycyrrhizin (GL), an inhibitor of HMGB1, was used to investigate whether the inhibition of HMGB1 modulated microglial M1/M2 polarization or attenuated brain damage after HI. HAPI microglial cells and primary neurons were cultured in vitro and an oxygen-glucose deprivation model was established to evaluate the effects of different microglial-conditioned media on neurons using GL and recombinant HMGB1. Results showed that the expression of HMGB1 was increased in both the ipsilateral cortex and peripheral blood 72 h after HI. Immunofluorescence analyses showed that HMGB1 in the cortex was primarily expressed in neurons. This increase in cortical HMGB1 expression 72 h after HI was characterized by increased co-expression with microglia, rather than neurons or astrocytes. The expression of both M1 and M2 microglia was upregulated 72 h after HI. The administration of GL significantly suppressed M1 microglial polarization and promoted M2 microglial polarization. Meanwhile, GL pretreatment significantly alleviated brain edema and cerebral infarction. In vitro experimentation showed that HMGB1-induced M1-conditioned media aggravated neuronal damage, but this effect was neutralized by GL. These ﬁndings suggest that HMGB1 may result in an imbalance of M1/M2 microglial polarization in the cortex and thus cause neuronal injury. Pharmacological blockade of HMGB1 signaling may attenuate this imbalanced polarization of microglia and thus could be used as a therapeutic strategy against brain injury in HIBD.